Reducing Healthcare-Associated Infections Through Coordinated Medical Department Interventions: A Systematic Review Of Practices, Compliance, And Outcomes (The Review of Diabetic Studies, 2024)
Background: Healthcare-associated infections (HAIs) remain a major global challenge, contributing significantly to patient morbidity, mortality, prolonged hospital stays, and increased healthcare costs. Despite the availability of evidence-based infection prevention guidelines, fragmented implementation across individual medical departments continues to limit their effectiveness.Objective: This systematic review aims to evaluate the impact of coordinated infection control interventions across medical departments on compliance, clinical effectiveness, and patient- and system-level outcomes in healthcare settings.Methods: A systematic search was conducted across major electronic databases, including PubMed, Scopus, Web of Science, and CINAHL, following PRISMA 2020 guidelines. Studies published between 2015 and 2025 that examined multidisciplinary or cross-departmental infection control interventions in healthcare environments were included. Data were synthesized narratively, focusing on intervention types, adherence mechanisms, and reported outcomes.Results: The reviewed evidence demonstrates that coordinated, system-level infection control strategies—such as shared protocols, multidisciplinary committees, integrated surveillance, and compliance monitoring—are consistently associated with reduced HAI rates, improved adherence to infection prevention practices, enhanced patient safety, and improved organizational performance.Conclusion: Coordinated medical department interventions represent a critical determinant of successful infection control. Strengthening interdisciplinary collaboration and compliance mechanisms is essential for sustainable HAI reduction and quality improvement in healthcare systems.